Intrapartum Cervical Laceration and Subsequent Pregnancy Outcomes - Wong, Luchin F.; Wilkes, Jacob; Korgenski, Kent; Varner, Michael W.; Manuck, Tracy A. (American Journal of Perinatology Reports, 2016)
Objective The objective of this study was to describe pregnancy outcomes, including cervical insufficiency and preterm birth, in the subsequent pregnancy following an intrapartum cervical laceration.Study Design Retrospective cohort of women with their first two consecutive singleton pregnancies carried to ≥ 200/7 weeks' gestation within a tertiary health care system from 2002 to 2012. Cervical laceration cases were identified by ICD9 codes and included if suture repair was required.Results In this study, 55 women were confirmed to have a cervical laceration in the first delivery; 43 lacerations after vaginal delivery (VD) and 12 after cesarean delivery (CD). The median gestational age of the first delivery was 400/7 weeks and the median birth weight 3,545 g; these did not differ between VD and CD. In the second pregnancy, 2 of 55 women (4.6%) had a prophylactic cerclage placed; 1 carried to term and the other delivered at 356/7 weeks. In total, four women (9.3%) delivered the second pregnancy < 37 weeks: three had a prior term VD and one had a prior 34 weeks VD. There was only one case of recurrent cervical laceration, occurring in the setting of vaginal deliveries.Conclusion Obstetric cervical lacerations are uncommon. Complications in the following pregnancy were low, despite lack of additional prophylactic cerclage use.
Keywords: cervical laceration; cervical trauma; cervical insufficiency; preterm birth